The Use of Mini Dairy In Teaching Writing - Nining Kurniah; Jajat Imanudin (Ridwan Institute, 2021)
This research is to find out that mini diary as media can generate the students’ ability in teaching writing. This research will be based on quantitative and qualitative study. To find out whether mini diary is effective or not in teaching writing recount text of eighth grade students of SMPN 4 Kuningan, the writers analyzed the data using t- test formula. The means score of pre-test of the experimental group is 66,56 and the post-test is 77.09. While the score of pre- test of the control group is 67 and the post- test is 72,5. The result shows that there is significant difference of mean score of the post test in both of the class. In the end of teaching writing recount text, the students’ achievement rises as 10,53 while in control class only rise as 5,5. After calculating the data, writers gets that t-observation (to) = 2,56 and with degree of freedom (df) as 74 and significant level 5%, t-table (tt) = 1.67. In this research, mini diary as media can increase the students’ enthusiasm to learn writing. It is shown by the students who pay attention while they are writing their experiences in mini diary. They are also active ask to the teacher when they did not understand or not know how to write correct sentences. Therefore, using mini diary as media makes class atmosphere more fun and comfortable.